The Role of the Educational Program in Reducing the Child's Anxiety at the Dentist - Ramona Vlad; Adriana Mihai; Monica Monea (European Scientific Journal, ESJ, 2023)
The objective of the study was to create and implement an educational program with the aim of reducing children's anxiety at the dentist. The study began with the hypothesis that the implementation of an educational program can lead to a decrease in the level of dental anxiety among children. The sample included 196 children (experimental group of 95 children and control group of 101 children), primary school pupils. The educational program was structured in the form of twelve PowerPoint presentations, focusing on three essential themes. These were: the importance of oral hygiene, methods and techniques used for good oral hygiene and the role of nutrition in maintaining healthy teeth. The methods used were the questionnaire, PowerPoint presentations, semi-structured interviews, demonstrations and exercises. A questionnaire was applied and saliva was taken to determine immunoglobulin A, both at the beginning and at the end of the study. In the experimental group, there were statistically significant differences between the initial and final results of both the questionnaire and immunoglobulin A testing (p<0.05). There were no statistically significant differences in the control group (p>0.05). Following the interpretation of the results, the hypothesis was confirmed according to which the implementation of an educational program can lead to a decrease in the level of dental anxiety in children.